Prescription Opioid Use Among Patients With Acute Gout Discharged From the Emergency Department. Issue 8 (5th July 2020) - Dalal, Deepan S.; Mbuyi, Nadine; Shah, Isha; Reinert, Steven; Hilliard, Ross; Reginato, Anthony
Abstract : Objective: Acute gout is among the most painful inflammatory arthritides and a frequent cause of emergency department (ED) visits. Prescription opioids are the leading contributor to the ongoing opioid epidemic; EDs are often the source of the index prescription. Our aim was to assess the burden of opioid use and factors associated with its use among gout patients discharged from the ED. Methods: In the electronic health records system of Lifespan Healthcare System (currently contains 2.2 million records), adult gout patients discharged from the ED or hospital were identified using International Classification of Diseases, Ninth Revision or Tenth Revision diagnostic codes. The study period was March 2015 to September 2017, and only patients with a primary diagnosis of gout were included. If a patient was seen multiple times, only the first encounter was included. For these patients, we estimated the frequency, dose, and duration of opioids prescribed. Using multivariable logistic regression, we ascertained the factors associated with increased odds of opioid prescription at discharge among patients with acute gout. Results: Of the 456 patients, 129 (28.3%) received opioids at discharge (~80% were new patients). The average dose of prescription was mean ± SD 37.9 ± 17.2 mg of morphine equivalent for a median duration of 8 days (interquartile range 5–14). We noted that patients with polyarticular gout attack and diabetes mellitus and those taking opioids prior to admission had higher odds of receiving opioids at discharge. Conclusion: Despite the availability of effective treatments, opioids are commonly used for the management of acute gout. This study highlights an opportunity to curb the opioid epidemic among gout patients.